A socially responsive university - Mariekie Burger (Communicare)
The lens of decolonisation invites the opportunity to reflect on the current mainstream views regarding the purpose of the public university. A decolonized approach suggests that the key tasks of a university (teaching, research and community engagement) should be socially responsive. This conceptual article draws on a class project to suggest a way in which the three tasks can be combined to respond so a particular social need. Against the foil of a class project - situated in a larger Izindaba Zokudla (conversations about food) community engagement project of the University of Johannesburg – this article argues: 1) instead of conventional teaching methods, teaching should be based on an empowerment education model; 2) instead of a top-down externally initiated model, community engagement should use a participatory multistakeholder approach; and 3) instead of conventional research approaches, research should be transformative. The article concludes, firstly that it is possible to integrate the teaching, research and community engagement tasks of a public university productively, and secondly, it should take as point of departure empowerment education, participatory community engagement, and transformative research.